Nutrition Education Intervention Via Instagram among Adolescents: A Scoping Review - Simatupang, Abdul Malik; Dewi, Yulia Lanti Retno; Andayani, Tri Rejeki (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Adolescence is a phase of rapid and critical development, necessitating increased energy, protein, vitamin and mineral requirements. However, poor dietary patterns during adolescence pose a risk factor for malnutrition, negatively impacting health into adulthood and, requiring nutritional interventions to break the cycle intergenerational malnutrition. Social media-based nutritional interventions through instagram have the potential to provide health information for adolescents. Objective: This study aimed to evaluate the development stages of intervention media and the effectiveness of nutritional education interventions through instagram addressing adolescent nutritional issues. Method: The study follows Arksey and O'Malley framework with PRISMA-ScR systematic review method. Article searches were conducted on Google, Scopus, Science Direct, PubMed and Google Scholar databases using keywords "nutritional education" OR "nutrition-related interventions" AND "Instagram" OR “Instagram-based” AND "adolescent". Inclusion criteria required articles published between 2014 and 2024, involving adolescents aged 10-19 years, written in English or Indonesian, instagram as primary intervention media and employing quantitative and qualitative research designs. Results: Review results indicated interventions lasting an average duration of 2-12 weeks with varying content, although detailed reporting on content development was often lacking. Despite predominantly low intensity, interventions across 12 demonstrated significant improvement in knowledge, attitudes, practices, diet quality, compliance in consuming iron folic acid supplementation (IFAS), waist circumference, physical activity, nutritional intake (energy, protein, carbohydrates), and body image. Nutritional education interventions through instagram showed varying degrees of success among adolescents. Conclusions: Overall, this review highlights the need for the development stages and the importance of considering intervention intensity to enhance the effectiveness of nutritional education interventions through instagram.